In the shadow of the swastika - Wygoda, Hermann (University of Illinois Press, 1998)
First days of the war -- Kossow -- My decision -- My brother is taken, again -- Twice arrested -- Liquidation of the Sokolow ghetto -- Twice saved by intuition -- Escape to Berlin -- In Berlin, again -- Three times to the rescue -- Escape to Italy -- Arrested, once again -- Recruited by the partisans -- Negotiations with a German commander -- Execution of a Nazi -- We liberate Savona -- Finding a new home -- Afterword.